(3YfhGf GdEaGOI dENhGf GdESJaGOgs - (3eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdCfOdSj GdQGYis; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s ((3CMeO Hf CHj HcQ GdSfai GdeGdci s)
(3ChdgG (B:s
(3bGd GdYHO GdabjQ eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdCfOdSi CeG HYO aEfg deG cGf Yde GdYQHjI ef CYXe GdYdhe hdeG cGfJ ebOeI GdTjN GdCSJGP GdfMhi CHj YHO Gddg eMeO Hf eMeO GdUfgGLi GdeTghQ HGHf BLQhe eJQLeI Ydi Gdege ef CHhGH GdYQHjI s
(3BNQgG (B:s
(3hbGd GHf eGdc QMeg Gddg Cfg bO dGjLhR GdaUd ai GdEVWQGQ HCLfHi hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf hSde JSdjekG cKjQkG Edi jhe GdOjf Je cJGH YfhGf GdEaGOI dENhGf GdESJaGOI hgh TQM GdLQhejI ai GdYQHjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3dgG fSNI CNQi efgG JMJ Qbe (B113 (3fMh s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs